ANALISA OIL LOSSES PADA MESIN PRESS DENGAN MENGGUNAKAN METODE STATISTICAL PROCESS CONTROL PADA INDUSTRI KELAPA SAWIT DI SUMATERA BARAT - Guntur, Guntur; Zulhamidi, Zulhamidi (Politeknik ATI Padang, 2021)
One of the industries that processes FFB (Fresh Bunches) into crude oil or also called Crude Palm Oil (CPO) and palm kernel or also called kernel in West Sumatra. In carrying out the production process, we always prioritize quality and always optimize the results of Crude Palm Oil (CPO) and kernel processing results. One of the ways to get optimal results is to reduce oil loss during the production process. From the data obtained, the analysis of press machine oil loss will be carried out using statistical process control (SPC) methods. After analyzing the oil loss at the press station, it was found that the oil loss analysis was not statistically controlled. Next, from this analysis, the cause of the problem that causes the loss of oil at the press station is sought. The cause of the problem is the work environment, people, work methods, raw materials and machines. Next, after the root of the problem is found, the author gives suggestions for improvement to each root of the problem found.